The principle of lexical co-information in the formation of a sexual dictionary - قادر, کاروان عومەر; براهیم, شیلان ڕەحیم إ (Sulaimani Journal for Humanities, 2025)
This study addresses the definition and clarification of the dimensions of the concept of "vocabulary knowledge" and its analysis in the Kurdish language according to one of the theories of cognitive linguistics, namely the "use-centeredness" theory. According to this theory, vocabulary knowledge is formed as an inevitable result of its use by language users, and "linguistic competence" is nothing but experience in using the language. A user's knowledge of a word lies in how they use it within expressions, sentences, and linguistic texts, and this knowledge shapes and forms the mental lexicon of language users. Cognitive linguistics in general, and the (use-centered) theory in particular, is concerned with human cognitive abilities such as (impression, observation, point of view, discrimination, classification, etc.) and praises the role of these abilities in creating expressions and sentences in language and the extent of their effects on grammatical structure and in formulating the rules of language.